A multi-scalar approach to marine survey and underwater archaeological site prospection in Murujuga, Western Australia. (20th May 2021) - Wiseman, Chelsea; O'Leary, Michael; Hacker, Jorg; Stankiewicz, Francis; McCarthy, John; Beckett, Emma; Leach, Jerem; Baggaley, Paul; Collins, Charles; Ulm, Sean; McDonald, Jo; Benjamin, Jonathan
Abstract: During the past 20, 000 years approximately one-quarter of the continental landmass of Australia was inundated by postglacial sea-level rise, submerging archaeological evidence for use of these landscapes. Underwater archaeological sites can offer substantial insights into past lifeways and adaptations to rapidly changing environments, however the vast scale of inundation presents a range of challenges in discovering such sites. Here we present a suite of methods as a model methodology for locating sites in submerged landscapes. Priority areas for survey were based on palaeoenvironmental contexts determined from the onshore archaeological record. Remote sensing was used to identify seabed composition and indicators of palaeolandscapes where high potential for human occupation and site preservation could be identified in Murujuga (or the Dampier Archipelago), northwestern Australia. Target locations were surveyed by scientific divers to test for the presence of archaeological material. Application of this methodology resulted in the discovery of the first two confirmed sub-tidal ancient Aboriginal archaeological sites on Australia's continental shelf. Survey methods are discussed for their combined value to identify different classes of landscapes and archaeological features to support future underwater site prospection.